Elastic flow instabilities and macroscopic textures in graphene oxide lyotropic liquid crystals - Jacek K. Wychowaniec (Nature Portfolio, 2021)
Abstract Graphene oxide (GO) forms a well-aligned lyotropic liquid crystal (LC) phase in aqueous dispersions at relatively low concentrations. Under a remarkably wide range of shear rates, we report hitherto unobserved shear-induced polarized light image patterns, a Maltese cross combined with shear banding, recorded in real time and in situ during rheological measurements. This is shown to be a result of elastic flow instabilities that manifest as a helical flow in alternating bands of left- and right-handed helices, arising from a combination of shear flow and Taylor-type vortex flow. The instability is observed for LCs formed from large aspect ratio GO particles owing to their unique viscoelastic properties, but not for smaller aspect ratio particles. This phenomenon coincides with rheopecty and anomalous small-angle X-ray scattering patterns under shear flow, which confirm the instabilities. The results presented here could lead to advanced control over macroscopic periodic alignment in technologically relevant dispersions of two-dimensional material particles.